Shikonin induces apoptosis and prosurvival autophagy in human melanoma A375 cells via ROS-mediated ER stress and p38 pathways. Issue 1 (4th December 2019) - Liu, Yongkang; Kang, Xing; Niu, Geng; He, Senlin; Zhang, Tingting; Bai, Yuwei; Li, Yi; Hao, Houyan; Chen, Chao; Shou, Zhexing; Li, Bin
Abstract: Shikonin, a botanical drug extracted from Lithospermum erythrorhizon, exhibits anti-cancer effects in various cancer cell lines. However, the mechanisms underlying these effects have not been completely elucidated yet. Here, we showed that Shikonin induces apoptosis and autophagy in A375 cells and inhibits their proliferation. Shikonin caused G2/M phase arrest through upregulation of p21 and downregulation of cyclin B1. Shikonin significantly triggered ER stress-mediated apoptosis by upregulating the expression of p-eIF2α, CHOP, and cleaved caspase-3. It also induced protective autophagy by activating the p38 pathway, followed by an increase in the levels of p-p38, LC3B-II, and Beclin 1. Upon suppression of autophagy by 3-methyladenine, Shikonin-induced apoptosis was enhanced in A375 cells. Moreover, after pretreatment with N -acetyl-cysteine, Shikonin increased the production of reactive oxygen species that are involved in regulating ER stress-mediated apoptosis and p38-activated autophagy, as evidenced by the reversion of cell viability and apoptosis and a decrease in p-eIF2α, CHOP, p-p38, LC3B-II, and Beclin 1 levels. Thus, we demonstrated that Shikonin induced apoptosis and autophagy in A375 cells via the activation of ROS-mediated ER stress and p38 pathways, indicating that Shikonin can serve as a potential agent for human melanoma therapy.